Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Srinivasan, A.; Giri, Ashok P.; Harsulkar, Abhay M.; Gatehouse, J. A.; Gupta, Vidya S. (Plant Molecular Biology, 2005)
Chickpea (Cicer arietinum L.) seeds contain Bowman-Birk proteinase inhibitors, which are ineffective against the digestive proteinases of larvae of the insect pest Helicoverpa armigera. We have identified and purified a low expressing proteinase inhibitor (PI), distinct from the Bowman-Birk Inhibitors and active against H. armigera gut proteinases (HGP), from chickpea seeds. N-terminal sequencing of this HGP inhibitor revealed a sequence similar to reported pea (Pisum sativum) and chickpea alpha-L-fucosidases and also homologous to legume Kunitz inhibitors. The identity was confirmed by matrix assisted laser desorption ionization - time of flight analysis of tryptic peptides and isolation of DNA sequence coding for the mature protein. Available sequence data showed that this protein forms a distinct phylogenetic cluster with Kunitz inhibitors from Glycine max, Medicago truncatula, P. sativum and Canavalia lineata. The isolated coding sequence was cloned into a yeast expression vector and produced as a recombinant protein in Pichia pastoris. alpha-L-fucosidase activity was not detectable in purified or recombinant protein, by solution assays. The recombinant protein did not inhibit chymotrypsin or subtilisin activity but did exhibit stoichiometric inhibition of trypsin, comparable to soybean Kunitz trypsin inhibitor. The recombinant protein exhibited higher inhibition of total HGP activity as compared to soybean kunitz inhibitor, even though it preferentially inhibited HGP-trypsins. H. armigera larvae fed on inhibitor-incorporated artificial diet showed significant reduction in average larval weight after 18 days of feeding demonstrating potent antimetabolic activity. The over-expression of this gene in chickpea could act as an endogenous source of resistance to H. armigera.
Keywords: Chickpea; Cicer arietinum; fucosidase; Helicoverpa armigera; Kunitz; Proteinase inhibitor

Differentially expressed gene transcripts in roots of resistant and susceptible chickpea plant (Cicer arietinum L.) upon Fusarium oxysporum infection - Nimbalkar, Suhas B.; Harsulkar, Abhay M.; Giri, Ashok P.; Sainani, Mohini N.; Franceschi, Vincent R.; Gupta, Vidya S. (Physiological and Molecular Plant Pathology, 2006)
Differentially expressed genes in chickpea, (Cicer arietinum L.) during root infection by Fusarium oxysportan f sp. ciceri Racel, were identified using cDNA-RAPD and cDNA-AFLP approaches. The former employed decamer primers on cDNA template and revealed nine differentially expressed transcripts in the resistant-infected chickpea variety. Among the 2000 transcript-derived fragments (TDFs) screened by cDNA-AFLP, 273 were differentially expressed in chickpea roots during Fusaritan infection. Only 13.65% of the TDFs were differentially regulated during pathogen challenge, while the other 86% were expressed non-differentially during the process of pathogen infection in chickpea roots. Nineteen TDFs, which expressed differentially in the resistant-infected chickpea variety were cloned and sequenced. Two of these TDFs were similar to transcription factors like WRKY proteins and 14-3-3 proteins, while three TDFs represented the NBS-LRR-type gene sequences. Two TDFs had sequence identity to genes known to have function in defense. The RAPID TDF CaFRi60 showed sequence identity to gamma-glutamyl-cysteine synthetase. Among the TDFs examined by cDNA-AFLP, 19 were confirmed by Reverse Northern blot to be differentially expressed. The data confirms the effectiveness of the cDNA-AFLP technique in detecting differentially expressed genes during pathogenesis. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cDNA-AFLP; Chickpea; Cicer arietinum; differentially expressed genes; fusarium oxysporum; Transcriptome

Relatedness of Indian flax genotypes (Linum usitatissimum L.): an inter-simple sequence repeat (ISSR) primer assay - Rajwade, Ashwini V.; Arora, Ritu S.; Kadoo, Narendra Y.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Molecular Biotechnology, 2010)
The objective of this study was to analyze the genetic relationships, using PCR-based ISSR markers, among 70 Indian flax (Linum usitatissimum L.) genotypes actively utilized in flax breeding programs. Twelve ISSR primers were used for the analysis yielding 136 loci, of which 87 were polymorphic. The average number of amplified loci and the average number of polymorphic loci per primer were 11.3 and 7.25, respectively, while the percent loci polymorphism ranged from 11.1 to 81.8 with an average of 63.9 across all the genotypes. The range of polymorphism information content scores was 0.03-0.49, with an average of 0.18. A dendrogram was generated based on the similarity matrix by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), wherein the flax genotypes were grouped in five clusters. The Jaccard's similarity coefficient among the genotypes ranged from 0.60 to 0.97. When the omega-3 alpha linolenic acid (ALA) contents of the individual genotypes were correlated with the clusters in the dendrogram, the high ALA containing genotypes were grouped in two clusters. This study identified SLS 50, Ayogi, and Sheetal to be the most diverse genotypes and suggested their use in breeding programs and for developing mapping populations.
Keywords: ALA; Alpha linolenic acid; Diversity assessment; Linseed; Oil content; Omega-3 fatty acid

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed

Production of polyunsaturated fatty acids in recombinant lipomyces starkeyi through submerged fermentation - Salunke, Devyani; Manglekar, Rupali; Gadre, Ramchandra V.; Nene, Sanjay; Harsulkar, Abhay M. (Bioprocess and Biosystems Engineering, 2015)
Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60 % of its biomass and where genetic transformation can be achieved. In our earlier work, Delta 15 desaturase gene (AEP37840) from flax was transformed into L. starkeyi. In the present work, we report optimization of medium for the production of omega-3 enriched oil from this transformed yeast. A basic medium containing 20 g/l glucose as a carbon source and 10 g/l yeast extract as a nitrogen source was used during fermentation. At regular time intervals, glucose was fed to maintain high C:N ratio (65:10) during fermentation. Under the most favorable conditions, dry biomass and total lipid content were 18 and 7.29 g/l, respectively. Prior to genetic transformation, L. starkeyi contained 56.03 mg/l DHA along with 71.4 mg/l EPA and 42.2 mg/l ALA. Genetic engineering of this yeast resulted in a strain that produced 1080 mg/l DHA (17.4 %) along with 74.28 mg/l EPA and 126.72 mg/l ALA possibly through modification of PUFA biosynthetic pathway. To the best of our knowledge, this is a first report of DHA enrichment and opens up avenues for LCPUFA production through L. starkeyi.
Keywords: Fermentation; LCPUFA; Lipid production; Oleaginous yeast

Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin